The role of artificial intelligence in drug screening, drug design, and clinical trials - Wu, Yuyuan; Ma, Lijing; Li, Xinyi; Yang, Jingpeng; Rao, Xinyu; Hu, Yiru; Xi, Jingyi; Tao, Lin; Wang, Jianjun; Du, Lailing; Chen, Gongxing; Liu, Shuiping (Frontiers in Pharmacology, 2024)
The role of computational tools in drug discovery and development is becoming increasingly important due to the rapid development of computing power and advancements in computational chemistry and biology, improving research efficiency and reducing the costs and potential risks of preclinical and clinical trials. Machine learning, especially deep learning, a subfield of artificial intelligence (AI), has demonstrated significant advantages in drug discovery and development, including high-throughput and virtual screening, ab initio design of drug molecules, and solving difficult organic syntheses. This review summarizes AI technologies used in drug discovery and development, including their roles in drug screening, design, and solving the challenges of clinical trials. Finally, it discusses the challenges of drug discovery and development based on AI technologies, as well as potential future directions.